2001
DOI: 10.1074/jbc.m106015200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Binding between Shiga Toxin and Receptor Glycolipid Gb3Cer by Surface Plasmon Resonance

Abstract: Shiga toxin (Stx) binds to the receptor glycolipid Gb3Cer on the cell surface and is responsible for hemolytic uremic syndrome. Stx has two isoforms, Stx1 and Stx2, and in clinical settings Stx2 is known to cause more severe symptoms, although the differences between the mechanisms of action of Stx1 and Stx2 are as yet unknown. In this study, the binding modes of these two isoforms to the receptor were investigated with a surface plasmon resonance analyzer to compare differences by real time receptor binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 51 publications
4
99
1
1
Order By: Relevance
“…Stx-1 and Stx-2 bind to different epitopes on the Gb3 molecule, and they also differ in binding affinity and kinetics (62). Surface plasmon resonance analysis showed that Stx-1 easily binds to and detaches from Gb3, in contrast to Stx-2, which binds slowly but also dissociates very slowly, thus staying on the cells long enough to be incorporated (62). The latter could explain why Stx-2 is 1000-fold more toxic than Stx-1 on human endothelial cells in vitro (63).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…Stx-1 and Stx-2 bind to different epitopes on the Gb3 molecule, and they also differ in binding affinity and kinetics (62). Surface plasmon resonance analysis showed that Stx-1 easily binds to and detaches from Gb3, in contrast to Stx-2, which binds slowly but also dissociates very slowly, thus staying on the cells long enough to be incorporated (62). The latter could explain why Stx-2 is 1000-fold more toxic than Stx-1 on human endothelial cells in vitro (63).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…The affinity of the selected aptamers to hIgG1-Fc was examined by surface plasmon resonance (SPR) using BIAcore 2000. Divalent kinetic parameters for each aptamer were estimated by curve fitting of the sensorgrams (Table 2; Nakajima et al 2001), reflecting the nuclear magnetic resonance (NMR) observation that two aptamers bind to one Fc (homodimer) unit (described below).…”
Section: Selection Of Igg Aptamersmentioning
confidence: 99%
“…SPR is performed by immobilizing glycolipids on a commercial SPR sensor chip, followed by exposure to unlabeled soluble GBPs (Kuziemko et al, 1996;MacKenzieet al, 1997;MacKenzie and Hirama, 2000;Nakajima et al, 2001). Binding is performed in a biosensor designed to detect mass bound to the sensor chip surface.…”
Section: Surface Plasmon Resonance (Spr) Spectroscopymentioning
confidence: 99%